2014
DOI: 10.1111/1574-6968.12469
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the lactococcal mevalonate pathway for increased sesquiterpene production

Abstract: Isoprenoids are a large, diverse group of secondary metabolites which has recently raised a renewed research interest due to genetic engineering advances, allowing specific isoprenoids to be produced and characterized in heterologous hosts. Many researches on metabolic engineering of heterologous hosts for increased isoprenoid production are focussed on Escherichia coli and yeasts. E. coli, as most prokaryotes, use the 2-C-methyl-d-erythritol-4-phosphate (MEP) pathway for isoprenoid production. Yeasts on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Mevalonate kinase was identified as a key gene for MK production in MG1363 as overexpression of mvk doubled the amount of MK produced. This result is in accordance with Song et al (2014) who identified mvk to be a metabolic bottleneck of the mevalonate pathway. Overexpression of other mevalonate genes did not result in greatly increased MK levels.…”
Section: Discussionsupporting
confidence: 92%
“…Mevalonate kinase was identified as a key gene for MK production in MG1363 as overexpression of mvk doubled the amount of MK produced. This result is in accordance with Song et al (2014) who identified mvk to be a metabolic bottleneck of the mevalonate pathway. Overexpression of other mevalonate genes did not result in greatly increased MK levels.…”
Section: Discussionsupporting
confidence: 92%
“…Most prokaryotes such as E. coli uses another terpenoid biosynthesis pathway called the 2-C-methyl- d -erythritol-4-phosphate (MEP) pathway, hence almost all metabolic engineering research for heterologous plant terpenoid production have been focussed on the MEP pathway of E. coli or the MVA pathway of yeast. At present, the lactococcal MVA accommodates much room for optimization as initial attempts to metabolically engineer this pathway resulted in more than doubling of sesquiterpenes produced [143]. …”
Section: Lactococcus Lactis As a Cell Factorymentioning
confidence: 99%
“…It also has been proven that cantharidin may derive from sesquiterpenes or be related to the biosynthesis of juvenile hormone. The FPPS is considered to be a key enzyme in the isoprenoid pathway and responsible for synthesizing the common precursor FPP for various essential isoprenoid end products, including sesquiterpenoids . Therefore, the extent of FPPS activity can directly alter the amount of the downstream diverse isoprenoids.…”
Section: Introductionmentioning
confidence: 99%